The Influence of Critical Reasoning, Independece, and Resilience to Adversity on The Numeracy Competence of 5th Grade Students in Cluster IV Kerambitan - Sari, I Gusti Martha (Universitas Wiralodra, 2023)
This study aims to determine the effect of critical reasoning, independence, and resilience to adversity on the numeracy competence of fifth-grade elementary school students in cluster IV Kerambitan. This research is ex-post-facto research. The population used as the sample in this study was 82 students. The independent variables in this study are critical thinking, independence, and resilience to adversity, while the dependent variable is the students' numeracy competence. Data collection methods used in this study were questionnaires and tests. Data on independence and resilience to adversity were collected using the questionnaire method, while data on students' critical thinking and numeracy competencies were collected using the test method. Data analysis used in this study is multiple regression and partial correlation. Based on the research that has been done, it is concluded that: 1) there is a significant influence of critical reasoning on the numeracy competence of fifth-grade elementary school students in cluster IV Kerambitan, with an effect of 40.8% and an effective contribution of 20.26%, 2) there is a significant effect of independence in the numeracy competence of fifth-grade elementary school students in cluster IV Kerambitan, with an effect of 48.9% and an effective contribution of 17.98%, 3) there is a significant effect of resilience to adversity on the numeracy competence of fifth-grade elementary school students in cluster IV Kerambitan, with an effect of 42% and an effective contribution of 28.41%, 4) taken together, there is a significant influence of critical reasoning, independence, and resilience to adversity on the numeracy competence of fifth-grade elementary school students in cluster IV Kerambitan, with an effect of 66.70%.